The study of the extended Higgs boson sector within 2HDM model - Obikhod, T.V.; Petrenko, E.A. (Вопросы атомной науки и техники, 2017)
Consideration of the latest experimental data on the searches for extended sector of Higgs bosons produced at the LHC at a center-of-mass energy of 13TeV, allows for computer modeling of the properties of supersymmetric particles within 2HDM model. The experimental restrictions on model parameters accounted in FeynHiggs code that is implemented in SusHi program, gave us the possibility to calculate the cross sections and branching fractions for three mechanisms of production and decay of Higgs bosons: 1) pp→H→ττ, 2) pp→A →Zh→llbb, 3) pp→H→ hh→bbττ at a center-of-mass energy of 14TeV. The considered computer modelling make it possible to draw conclusions about the need to take into account the b-associated production process of Higgs bosons for fermionic decay channel at large values of tanβ. Differential cross sections with respect to the Higgs transverse momentum pₜ and pseudorapidity η are calculated and the peculiarities of the kinematics of the Higgs boson decay products are recognized. Облiк останнiх експериментальних даних з пошуку розширеного сектора бозонiв Хiггса, отриманих на БАК при енергiї протон-протонного зiткнення 13 ТеВ, дозволяє провести комп’ютерне моделювання властивостей суперсиметричних частинок у рамках 2HDM-моделi. Експериментально отриманi обмеження на параметри моделi, якi врахованi в iмплементованому в SusHi кодi FeynHiggs, дали нам можливiсть порахувати перерiзи, ширини розпадiв для трьох механiзмiв народження i розпаду бозонiв Хiггса: 1) pp→H→ττ, 2) pp→A →Zh→llbb, 3) pp→H→ hh→bbττ при енергiї в системi центра мас 14 ТеВ. Розглянутi розрахунки дають можливiсть зробити висновки про необхiднiсть врахування b-асоцiйованого процесу народження бозонiв Хiггса для фермiонного каналу розпаду при великих значеннях параметра tanβ. Отримано розподiли диференцiальних перерiзiв по поперечному iмпульсу pₜ i по псевдошвидкостi η, i виявлено особливостi кiнематики продуктiв розпаду бозонiв Хiггса. Учет последних экспериментальных данных по поиску расширенного сектора бозонов Хиггса, полученных на БАК при энергии протон-протонного взаимодействия 13 ТэВ, позволяет провести компьютерное моделирование свойств суперсимметричных частиц в рамках 2HDM-модели. Экспериментально полученные ограничения на параметры модели, учтенные в имплементированном в SusHi коде FeynHiggs, дали нам возможность посчитать величины сечений, ширины распадов для трех механизмов рождения и распада бозонов Хиггса: 1) pp→H→ττ, 2) pp→A →Zh→llbb, 3) pp→H→ hh→bbττ при энергии в системе центра масс 14 ТэВ. Рассмотренные расчеты дают возможность сделать выводы о необходимости учета b-ассоциированного процесса рождения бозонов Хиггса для фермионного канала распада при больших значениях параметра tanβ. Получены распределения дифференциальных сечений по поперечному импульсу pₜ и по псевдобыстроте η, и выявлены особенности кинематики продуктов распада бозонов Хиггса.